Electrical storm is associated with impaired prognosis compared to ventricular tachyarrhythmias. (1st October 2019) - Behnes, Michael; Müller, Julian; Ellguth, Dominik; Schupp, Tobias; Taton, Gabriel; Reiser, Linda; Engelke, Niko; Reichelt, Thomas; Bollow, Armin; Kim, Seung-Hyun; Barth, Christian; Saleh, Ahmad; et al.
Abstract: Background: Because data on electrical storm (ES) is limited, this study sought to compare the prognosis of patients with ES to those with ventricular tachyarrhythmias on mortality, rehospitalization and major adverse cardiac events (MACE). Methods: In this retrospective study consecutive implantable cardioverter defibrillator (ICD) recipients presenting with ES were compared to patients surviving ventricular tachyarrhythmias (ventricular tachycardia (VT) or fibrillation (VF); non-ES) on admission from 2002 to 2016. The primary endpoint was all-cause mortality, secondary endpoints were rehospitalization and MACE at 2.5 years of follow-up. Results: 764 consecutive patients with an ICD were included (11% with ES, 89% with VTA). ES was associated with higher rates of all-cause mortality (37% vs. 20%, log-rank p  = 0.001; HR 2.084; 95% CI 1.416–3.065, p  = 0.001). However, only in secondary preventive ICD recipients, ES remained significantly associated with mortality (39% vs. 20%; log rank p  = 0.001; HR 2.235, 95% CI 1.378–3.625, p  = 0.001). Furthermore, ES was associated with higher rates of rehospitalization (44% vs. 12%, log-rank p  = 0.001; HR 4.763, 95% CI 3.237–7.009, p  = 0.001), mainly due to VT (22% vs. 4%, p  = 0.001) and acute heart failure (AHF) (17% vs. 4%, p  = 0.001) and higher rates of MACE (40% vs. 23%; log rank p  = 0.001; HR 1.838; 95% CI 1.273–2.654, p  = 0.002). Increasing risks of death and rehospitalization were still observed even after multivariable adjustment. Conclusion: ES was associated with increased rates of all-cause mortality, rehospitalization, respectively due to VT and AHF, as well as MACE at 2.5 years compared to patients with ventricular tachyarrhythmias apart from ES. Highlights: ES is associated with increased rates of long-term all-cause mortality. ES is not associated with all-cause mortality in primary preventive ICD recipients. ES is associated with increased rates of VT and AHF related rehospitalization. ES is associated with increased rates of MACE.